Competition and Price Dispersion in the U.S. Airline Industry - Borenstein, Severin; Rose, Nancy L. (Journal of Political Economy, 1994)
The authors study dispersion in the prices an airline charges to different passengers on the same route. This variation in fares is substantial: the expected absolute difference in fares between two passengers on a route is 36 percent of the airline's average ticket price. The pattern of observed price dispersion cannot easily be explained by cost differences alone. Dispersion increases on routes with more competition or lower flight density, consistent with discrimination based on customers' willingness to switch to alternative airlines or flights. The authors argue that the data support models of price discrimination in monopolistically competitive markets. Copyright 1994 by University of Chicago Press.